2021
DOI: 10.1007/s11845-021-02637-9
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate training in Cancer Genetics—a cross-specialty survey exploring experience of clinicians in Ireland

Abstract: Background As genomic profiling of constitutional and tumour-derived DNA becomes increasingly critical in cancer risk estimation, prognostication and treatment, there is a growing need for clinicians involved in cancer care to up-skill in Cancer Genetics. In the Republic of Ireland (ROI), this is particularly crucial, given a paucity of vocationally trained Clinical Geneticists per capita compared to other European countries. Aims We aimed to assess the self-reported co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…3,4 However, studies have indicated that integration of genomic data into 'mainstream' care is currently limited by clinicians' genomic literacy. [5][6][7][8] GeNotes is a new online 'just in time' educational resource for clinicians, it is being developed across specialties in collaboration with Health Education England's Genomic Education Programme. It aims to improve use of genomic testing by providing clinical information about specific tests, underpinned by opportunities to access broader genomics education.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, studies have indicated that integration of genomic data into 'mainstream' care is currently limited by clinicians' genomic literacy. [5][6][7][8] GeNotes is a new online 'just in time' educational resource for clinicians, it is being developed across specialties in collaboration with Health Education England's Genomic Education Programme. It aims to improve use of genomic testing by providing clinical information about specific tests, underpinned by opportunities to access broader genomics education.…”
Section: Introductionmentioning
confidence: 99%